EFFECT OF DESTINATION IMAGE, PERCEIVED QUALITY, PERCEIVED VALUE TO SATISFACTION AND REVISIT INTENTION IN TANJUNG BENOA BALI - Carla, Siane; Andajani, Erna; Rahayu, Siti (Journal Economics & Business Atmajaya Indonesia, 2017)
Interesting attractions will make tourists come back to visit and create a positive image of the tourist area. This study aimed to analyze the influence of Destination Image, Perceived Quality and Perceived Value on Satisfaction and Revisit Intention on tourism in Tanjung Benoa Bali. This study uses primary data through questionnaires on 150 travelers whove been to Water sport Tanjung Benoa Bali. The sampling technique of this study was non-probability sampling. Processing and testing the model using Structural Equation Modeling (SEM) with the help of analysis of moment structures (AMOS 16). The results of quantitative research shows that there is influence of destination image on perceived quality, perceived value on satisfaction and revisit intention significantly. The influence of perceived quality significantly to perceived value, satisfaction and revisit intention. Note also that there is the effect of perceived value on satisfaction and revisit intention. In this study also found that there is influence significant satisfaction to revisit intention.